FAKTOR YANG DIDUGA MENJADI RESIKO PADA ANAK DENGAN RINITIS ALERGI DI RSU DR. CIPTO MANGUNKUSUMO JAKARTA - Harsono, Ganung; Munasir, Zakiudin; Siregar, Sjawitri P; Suyoko, HEM Dadi; Kumiati, Mia; Evalina, Rita; Palupi, Ratih D (Jurnal Kedokteran Brawijaya, 2007)
This researach was aimed to describe the risk factor profile of pediatric patients with allergic rhinitis. 1792 medical recordsof outpatients pediatric allergy immunology clinic in Cipto Mangunkusumo Hospital from 1997 to 2005. Fifty patients were diagnosed with allergic rhinitis and 22% of them  were having allergic rhinitis with bronchial asthma.Allergic rhinitis were identified higher in boys (62%) than girls (38%) and ranged from 5 months to 13 years and 8 months old. Atopic history were identified in 24 patients (48) while atopic history in patient family were identified in mother (42%), father (40%), and siblings (24%). Total IgE serum increased in 35 patients (88,57%) while total eosinophil serum increased in 28 patients (80%). The most common aeroallergen by skin prick test was house dust mite (36%) and the most common food allergen was shrimp (40%). There were several factors that contribute to the development of allergic rhinitis such as age, sex, family atopic history and increasing in total IgE serum and total eosinophil serum . House dust mite and shrimp were the most common allergen identified in allergic rhinitis. Keywords: allergic rhinitis, risk factors, pediatric